Motherhood Penalty and Low Fertility in China: A Pseudo-Event Study - Wei Huang; Yiping Wang; Hantao Wu; Yi Zhou (Journal of Population Economics, 2025)
Using the census data from 2000-2015 and a pseudo-event study design, we estimate the motherhood penalty in China and explore its association with declining fertility. We find that one-third of working women leave their jobs in the year when they give birth, and the penalty persists for over eight years. The motherhood penalty increases significantly across almost all provinces during this period, and provinces with larger increases in the penalty experience greater declines in fertility rates. Using a mover-based design, we find that the rising motherhood penalty has caused a significant decline in the total fertility rate.